Design Method of Equivalent Driving Waveform Based on Electrowetting Response Characteristics - Tian, Lixia; Li, Hao (Frontiers in Physics, 2021)
As a new reflective display technology, electrowetting displays (EWDs) have many important characteristics, such as high reflectivity, low power consumption and paper-like display. However, the contact angle hysteresis in the driving process seriously affects the response speed of EWDs. According to the hysteresis phenomenon of contact angle in an oil switch motion with the action of interface tension, the brightness curve of EWDs in the process of pixel switching by different driving voltages was tested in this paper, and driving voltage was changed from 30V to 100V at the same time. Then, an equivalent driving waveform design method with overdriving voltage was proposed, and the overvoltage was set to 100V according to the hysteresis effect and driving characteristic of EWDs. Experimental results showed that the response rising time of EWDs was reduced to 21ms by using the proposed driving waveform, and the response performance of EWDs can be effectively improved.